OPERATION TECHNIQUE AND OPERATIONAL TIME CALCULATION OF PURSE SEINE IN FISH CAPTURE: A CASE STUDY ON KM. MUTIARA SEJATI - Liya Tri Khikmawati; Rakhma Fitria Larasati; Haikal Hidayat; Angkasa Putra; Sarifah Aini; Anita Syam; Hawati Hawati (Universitas Mataram, 2024)
A purse seine is an active fishing gear operated by encircling schools of fish. KM. Mutiara Sejati is one of the fishing vessels based in PPP Bajomulyo, Central Java, employing purse seine for small pelagic fisheries. That research aimed to explore the operational techniques of purse seine fishing gear and determine the time calculation for its operation. The study was conducted over five months, from October 2022 to March 2023, utilizing observation, interviews, and documentation as research methods. The operational area of the vessel was in the WPP 712 (Java Sea) with PPP Bajomulyo serving as the fishing base. Based on the research findings, the operational process of small pelagic purse seine began with a series of steps, including the deployment of fish aggregating devices, activation of vessel lights, deactivation of lights except for those at the stern, lowering of the boom lights, total shutdown of vessel lights, setting of the net, purse line retrieval, retrieval of the boom lights, net hauling process, catch retrieval, and ultimately, the re-arrangement of fishing gear. Calculation results indicated that the average operational time for the fishing gear during the nighttime was 87 minutes, while during the early morning hours, it was 83 minutes.